Complete mitochondrial genome of Basilepta melanopus Lefèvre, 1893 (coleoptera: chrysomelidae: eumolpinae), a tea pest from Southern China - Yonglin Liao; Yurong Fang; Weiping Chen; Jihua Wang (Mitochondrial DNA. Part B. Resources, 2024)
AbstractThe tea pest, Basilepta melanopus Lefèvre 1893 (Chrysomelidae), belongs to the subfamily Eumolpinae. In this study, the complete mitochondrial genome sequence of B. melanopus from southern China was sequenced using the next-generation sequencing technique, assembled, and annotated using bioinformatics tools. The complete mitochondrial genome was 15,905 bp in length. The overall GC content was 22.51%, in which the percentages for the bases A, T, C, and G were 41.23%, 36.26%, 8.92%, and 13.59%, respectively. Thirty-seven genes were predicted, including 13 protein-coding, 22 transfer RNA, and two ribosomal RNA genes. Phylogenetic analysis based on the complete mitochondrial genome sequences of 18 Chrysomelidae taxa revealed that B. melanopus was closely related to Basilepta fulvipes.